Comparative efficacy and safety of Chinese medicine injections combined with capecitabine and oxaliplatin chemotherapies in treatment of colorectal cancer: A bayesian network meta-analysis - Liu, Shuzhen; Zhang, Kun; Hu, Xianfang (Frontiers in Pharmacology, 2022)
Objective: The aim of the present Bayesian network meta-analysis (NMA) was to explore the comparative effectiveness and safeaty of different Chinese herbal injections (CHIs) combined with the XELOX regimen versus XELOX alone for colorectal cancer (CRC). Methods: A comprehensive search for randomized controlled trials (RCTs) was performed with regard to different CHIs for the treatment of CRC in several electronic databases up to April 2022. The quality assessment of the included RCTs was conducted according to the Cochrane risk of bias tool. Standard pair-wise and Bayesian NMA were designed to comparethe effectiveness and safety of different CHIs combined with the XELOX regimen by utilizing R 4.0.3 software and Stata 15.1 software simultaneously. Results: Initially, a total of 4296 citations were retrieved through comprehensive searching, and 32 eligible articles involving 2847 participants and 11 CHIs were ultimately included. CHIs combined with XELOX were superior to the XELOX regimen alone, and a total of ten Observation Indicators were included in the study, with the following results.Among all the injections, Shengmaiyin, Shenmai, and Kanglaite combined with the XELOX regimen were the three CHIs withthe highest clinical efficiency. The top three in terms of improving CD3+ values were Shengmaiyin, Shenqifuzheng, and Cinobufacini injections. Shenqifuzheng,Shengmaiyin, and BruceaJavanica oil injections combined with the XELOX regimen performed best at raising CD4+ values. Kanglaite, Cinobufacini, and Matrine injections combined with the XELOX regimen performed best in improving CD4+/CD8+ rates. The top three in terms of improving performance status were Xiaoaiping, Shenmai, and Kanglaite injections. Cinobufacini and Brucea Javanica oil injections combined with the XELOXregimen performed best at raising CD8+ values. Shenqifuzheng, Kangai, and Matrine injections combined with the XELOX regimen performed best in improving Gastrointestinal reactions.The top three in terms of improving Leukopenia were Shenqifuzheng, Compound Kushen and Kanglaite injections. The top three in terms of improving Platelet decline were Compound Kushen,Cinobufacini and Shenqifuzheng injections.Additionally, those that were best at improving nausea and vomitting were Cinobufacini, Compound Kushen and Aidi injections. Conclusions: The results of the analysis demonstrated that Shengmaiyin, Kanglaite, and Cinobufacini injections and the XELOX regimen were associated with more preferable and beneficial outcomes than others.